Ketahanan Psikologis pada Anak Jalanan: Dasar Pengembangan Layanan Intervensi bagi Konselor Komunitas - Aisyah, Iis; Antika, Eni Rindi (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The purpose of this study was to determine the level of psychological resilience of street children in Semarang Social Service Institutions. This study uses a quantitative approach with an ex post facto research design. This research was conducted at two locations, namely the Mandiri Children's Social Service Center in Semarang and the Wira Adhi Karya Social Service Center in Semarang. The population in this study amounted to 150 street children. The research sample was 110 street children who were taken by area random sampling technique. The research instrument used was a psychological resilience scale. This study uses validity and reliability tests. Based on the 70 statement items on the psychological resilience scale, there are 48 statement items that are declared valid and reliable. This study uses data analysis techniques, namely descriptive analysis. Based on the results of the descriptive analysis, it was revealed that the psychological resilience of street children in Semarang Social Service Institutions was in the moderate category with M = 135 and SD = 15.4. While the researchers also revealed based on the results of the descriptive analysis that street children are in the moderate category on each indicator of psychological resilience according to the theory of Connor & Davidson.